Batch alignment of single-cell transcriptomics data using deep metric learning - Xiaokang Yu; Xinyi Xu; Jingxiao Zhang; Xiangjie Li (Nature Communications, 2023)
The increasing scale of single-cell RNA-seq studies presents new challenge for integrating datasets from different batches. Here, the authors develop scDML, a tool that simultaneously removes batch effects, improves clustering performance, recovers true cell types, and scales well to large datasets.